OCT angiography for diagnosing and postoperative monitoring of serous maculopathy associated with optic disc pit - N.S. Lutsenko; O.A. Rudycheva; O.A. Isakova; A.N. Sergienko (Journal of Ophthalmology, 2019)
Background: Optic disc pits (ODP) usually present with the serous maculopathy found in 30% to 75% of these patients.